Neurologic music therapy for non-fluent aphasia: a systematic review and meta-analysis of randomized controlled trials - Gu, Jiayi; Long, Wei; Zeng, Siqin; Li, Chengjuan; Fang, Cuini; Zhang, Xiaoying (Frontiers in Neurology, 2024)
Introduction The efficacy of neurologic music therapy (NMT) techniques for the treatment of non-fluent aphasia has been widely accepted by the rehabilitation medical community. However, consensus on which dimensions of speech function can be improved by NMT techniques and standardized intervention dosage remains elusive. This study aimed to provide evidence regarding the efficacy of NMT in improving speech function and explore the optimal intervention dose. A systematic review and meta-analysis were conducted to search for randomized clinical trials and open-label trials that evaluated speech functions after NMT. Methods We searched all papers and reviews published from database inception to July 2023, including PubMed, Cochrane Library, Web of Science, Embase, and CNKI. Statistical analyses were mainly carried out on RevManV5.4.1 and pooled using a random-effects model. The primary outcome was the standardized mean difference (SMD) in speech functions, determined by calculating the change in speech functions score from baseline to the primary endpoint in the NMT group versus the control arm. Results A total of 11 studies with 329 patients were included. NMT had a positive effect on repetition ability (SMD = 0.37, 95%CI [0.12, 0.62], p < 0.05), but did not lead to significant differences in naming, comprehension, spontaneous speech, or communication. When the intervention time was >20 h, NMT exhibited a significant advantage at improving repetition ability (SMD = 0.43, 95%CI [0.06, 0.79], p < 0.05). Discussion This study provides evidence supporting the NMT enhancement of repetition ability in patients with non-fluent aphasia. Future large-sample studies are required to determine the optimal intervention dose of music therapy for different subtypes of non-fluent aphasia. Systematic review registration PROSPERO, identifier CRD42023470313.